Survey on the Preparation and Consumption Pattern of Smoked Dried Beef in Kerala - Rani, C.; Kuttinarayanan, P.; Oommen, George T.; Chungath, Jose John; Sunil, B. (Journal of Meat Science, 2014)
Idiyirachi is a traditional smoked dried beef available in hilly areas of Kerala. Hundred houses at Adimaly Gramapanchayat of Idukki district of Kerala were surveyed to document the information regarding method of preparation, ingredients used, packaging, storage and consumption of the product. Sun drying and/or smoking were the basic methods practiced to dry the meat. The representative sample when analysed for chemical composition varied non-significantly under different methods of preparation except acid insoluble ash. Aerobic plate count and yeast and mould count were significantly less in smoked beef samples.